Second Account Instagram sebagai Ruang Privasi dan Kepedulian Gen Z : Studi pada Dukungan Teman Sebaya - Manie Sari Ama Putri (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
A second account is a private Instagram account, meaning it cannot be viewed by everyone. Users will only be friends with their peers on the second account. Second accounts are often used by individuals concerned about negative comments if they post things without considering their image on the main account. This phenomenon of second accounts is also experienced by students at the University of Jember. Some students create second accounts for various reasons, but they serve the same purpose: as a private space to show a more honest side of themselves. In second accounts, semi-private communication occurs between users and their peers. Because of mutual knowledge of the lives of users and their peers, support arises from uploaded posts. This demonstrates closeness and caring between peers. Because of this support, students feel accepted and cared for by their peers. The purpose of this study was to increase insight and reading resources for University of Jember students regarding the usefulness of second accounts for Gen Z as both a private space and a space for caring. During the implementation, this researcher used a qualitative method with a phenomenological approach. The theory used in this study was Herbert Blumer's Symbolic Interactionism. The research location was at the University of Jember. The results of this study indicate that symbolic interactionism occurring on second accounts makes them a space for privacy and caring for Gen Z, particularly students at the University of Jember. Gen Z, especially students, use second Instagram accounts to post about their lives without having to worry about self-image. Through peer posts on these accounts, various forms of support emerge as a form of caring between friends. Keywords: caring, Instagram, privacy, peers, second account
:: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: Second Account